2017
DOI: 10.18571/acbm.120
|View full text |Cite
|
Sign up to set email alerts
|

CONTAMINAÇÃO AMBIENTAL POR OVOS DE Ancylostoma spp. E Toxocara spp. EM ÁREAS DE SEIS PRAÇAS PÚBLICAS DO MUNICÍPIO DE VALENÇA, ESTADO DO RIO DE JANEIRO

Abstract: <p>A contaminação de praças públicas por ovos de geohelmintos constitui um problema de saúde pública. Nesses locais, ovos ou larvas podem permanecer por muito tempo, até que a infecção ocorra. O objetivo deste trabalho foi verificar a contaminação ambiental por ovos de <em>Ancylostoma</em> spp. e <em>Toxocara </em>spp. em amostras de solos coletadas de praças públicas de Valença, Rio de Janeiro. O trabalho englobou seis praças próximas ao centro da cidade. Foram colhidos 50g de so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 15 publications
0
4
0
3
Order By: Relevance
“…Studies of frequency of parasites in the soil found in different Brazilian regions and in the world have shown environmental contamination of public places, mainly in regions where there is poor sanitation (Maikai et al, 2008;Santarém et al, 2009;Mello et al, 2011;Lima et al 2017). This study shows that the contamination index of public squares on the shore of Laranjal beaches was 8.3% whereas a previous study carried out on the same site found 9.5% positivity in the soil (Villela et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of frequency of parasites in the soil found in different Brazilian regions and in the world have shown environmental contamination of public places, mainly in regions where there is poor sanitation (Maikai et al, 2008;Santarém et al, 2009;Mello et al, 2011;Lima et al 2017). This study shows that the contamination index of public squares on the shore of Laranjal beaches was 8.3% whereas a previous study carried out on the same site found 9.5% positivity in the soil (Villela et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The parasitic structures found are the agents of diseases. Cutaneous larva migrans is caused by percutaneous penetration of the hookworm larvae or by oral ingestion (Cirne et al, 2017). Strongyloides sp.…”
Section: Discussionmentioning
confidence: 99%
“…Outros estudos brasileiros apresentaram frequências de contaminação do solo menores, como observados em Uberlândia -MG, onde 23,07% das 39 praças analisadas, estavam contaminadas (Costa-Cruz et al, 1994), em Campo Grande (MS), onde obteve-se 85,1% de positividade em ambientes públicos (Araújo et al, 1999), em Guarulhos -SP, onde das praças de 47 distritos, 74,5% apresentaram ovos e larvas de parasitas (Marques et al, 2012) e 66,6 % de positividades em seis praças analisadas do município de Valença -RJ (Cirne et al, 2017).…”
Section: Discussionunclassified
“…A maior frequência de Ancylostoma spp. na sua forma de larva e ovos encontrados nessa pesquisa foi semelhante aos Dipylidium caninum, também não apresentou tanta representatividade quando comparados aos demais helmintos intestinais de cães e gatos, fato também observado por outros autores (Cirne et al, 2017;Batista et al, 2019;Ferraz et al, 2019).…”
Section: Discussionunclassified